Considerations for utilizing medullary sponge kidney allografts in pediatric patients. (3rd April 2021) - Mahajan, Ruchi G.; Chang, Jae‐Hyung; Runge, Brian; Carpenter, Christina; Sandoval, Pedro R.; Ratner, Lloyd E.; Uy, Natalie S.; Jain, Namrata G.
Abstract: Background: Medullary sponge kidney (MSK) disease predisposes patients to recurrent nephrolithiasis, which affects one in every 5000 people in the United States. Methods: We report a rare case of a pediatric recipient of a living donor MSK transplant and discuss considerations when discussing risks and benefits of accepting MSK allografts for this population. Results: The recipient was admitted due to concerns for nephrolithiasis, hydronephrosis, and urinary tract infection at 1‐month post‐transplant. The hydronephrosis was resolved by surgical removal of an encrusted ureteral stent; this was followed by supplementation with oral medications to prevent future episodes of nephrolithiasis. The recipient did not have any further episodes after this as seen at a 1‐year follow‐up. The donor has remained well through this period. Conclusions: With increasing organ shortages, the use of variety of donors may need to be considered to enlarge the organ pool.